Pengangkatan Menteri dalam Sistem Presidensial di Indonesia Perspektif Imam Al-Mawardi - Paramadina, Panggih Fadhilla; Al Arif, M. Yasin (Universitas Islam Negeri Raden Intan Lampung, 2021)
The election of ministers on Wednesday, October 23, 2019 by President Joko Widodo sparked public controversy, for appointing the figure of Fachrul Razi as Minister of Religion. Fachrul Razi is considered controversial, because his background comes from the military and has no history of joining a religious base. Apart from that, the fatness of the Advanced Indonesia Cabinet is undeniably a result of the fat coalition supporting the Jokowi-Ma'ruf Amin government, the fat coalition has an impact on the weak opposition which should play an important role in controlling government policies, while the fat coalition in the Advanced Indonesia Cabinet has the potential to make the decision-making process worse. The effectiveness of the decision is reduced. Because of this, the author interested in studying how the ministerial implementation should be in accordance with Law No. 39 of 2008 concerning the Ministry by using the perspective of Imam Al-Mawardi in the appointment of wazir (assistant caliphs) who are in harmony with the appointment of ministers in Indonesia. The purpose of this research is to provide a breakthrough to examine the system of appointing ministers in accordance with Islamic law. One approach that can be used as an example is to use Imam Al-Mawardi's perspective analysis in reviewing the ministerial appointment system in the government structure in Indonesia. The government structure in Indonesia through the analysis of Imam Al-Mawardi's perspective is of course in accordance with Islamic law and can be carried out by the President by always fulfilling the requirements and appointment procedures as stipulated in Law No. 39 of 2008 concerning the Ministry. The method used in this study uses two approaches to get valid results, namely the conceptual approach and the statutory approach.